The Recommendation to Wear Hijab and the Phenomenon of the Rise of Dating Among Young People in Indonesia: A Review of Islamic Law - Nahdiyatul Auliyah Nursyahadah; Didik Himmawan; Ghea Salsabila (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
Indonesia is known as a country with diverse tribes, cultures, races, and religions. Each religion has differences that can create conflicts between religious communities. So it is necessary to apply an attitude of tolerance in society. The teachings of tolerance are related to Islam. Islam also provides freedom for anyone to embrace the religion they believe in. Islam is also a pioneer of tolerance in creating peace and harmony in religious life. The  purpose of this study was to determine the Hijab and the Dynamics of Dating in Young People in the Review of Islamic Law. This study is expected to be a source of knowledge. The type of research used is qualitative research. The literature sources used are books, e-books, journals, articles, and trusted websites. Literature sources are collected using search engines, and through libraries. Literature sources are then analyzed and concluded, the results of the literature study are made into a systematic narrative by citing and referring to literature sources. The writing format is adjusted to applicable scientific principles and guidelines. The results of this study are that the law of wearing the hijab according to Islam is mandatory for women, and the law of dating according to Islam is forbidden because it can bring us closer to various forms of adultery.